Complete and durable remission of human epidermal growth factor receptor 2-positive metastatic urothelial carcinoma following third-line treatment with trastuzumab and gemcitabine - Wezel, Felix; Erben, Philipp; Gaiser, Timo; Budjan, Johannes; Hardenberg, Jost von; Michel, Maurice Stephan (Urologia internationalis, 2018)
Urothelial carcinoma (UC) is one of the most common cancers and survival rates are low in metastatic disease with currently established first-line platinum-based chemotherapies. Unlike in many other cancers, no clinically established molecular targeted therapies exist for the treatment of this malignancy. Here we present a case of complete tumor remission following third-line treatment with trastuzumab and gemcitabine in a patient with human epidermal growth factor receptor 2 (HER2)-positive UC after progression under cisplatin and vinflunine chemotherapies. This case shows the potential significance of anti-HER2 therapy in selected patients with molecularly characterized UC. Clinical trials so far show inconclusive outcomes of anti-HER2 therapies in UC, indicating further need for both basic research and clinical studies for the identification of resistance factors and improved patient selection.